An Unhealthy Buying Pattern of the Peoples of Bangladesh: A Case of Tobacco & Beverage - Niloy, Ahnaf Chowdhury (Asian Business Review, 2020)
Bangladesh is a comparatively small country but a densely populated country that has attracted several big companies to come and run their business including carbonated drinks and tobacco. International beverage brands like coca-cola, Pepsi, etc., and tobacco brands like British American Tobacco, Philip Morris International, etc. are doing great business in Bangladesh alongside local brands. Even though for business, these products are a must but when it comes to health issues these are such products that affect physically greatly. Matter of consciousness comes when the consumer is giving preference to such products more than essential consumables that are seen in Bangladesh. The paper discusses the consumer behavior of Bangladeshi consumers in choosing products in terms of health benefits. The paper is an original work of the author and all the secondary data were taken are given credits properly.